Remaking Birmingham : the visual culture of urban regeneration - Kennedy, Liam, 1946- (Routledge, 2004)
The volume is multi-disciplinary in content, including contributions from specialists in architecture, public and community arts, photography and urban studies - their critical perspectives linked by interest in urban visual culture.